PERMEABILITY CHANGES DUE TO MINERAL DIAGENESIS IN FRACTURED CRUST: IMPLICATIONS FOR HYDROTHERMAL CIRCULATION AT MID-OCEAN RIDGES - Fontaine F.J.; Rabinowicz M.; Boulegue J. (My University, 2001)
The hydrothermal processes at ridge crests have been extensively studied during the last two decades. Nevertheless, the reasons why hydrothermal fields are only occasionally found along some ridge segments remain a matter of debate. In the present study we relate this observation to the mineral precipitation induced by hydrothermal circulation. Our study is based on numerical models of convection inside a porous slot 1.5 km high, 2.25 km long and 120 m wide, where seawater is free to enter and exit at its top while the bottom is held at a constant temperature of 420°C. Since the fluid circulation is slow and the fissures in which seawater circulates are narrow, the reactions between seawater and the crust achieve local equilibrium. The rate of mineral precipitation or dissolution is proportional to the total derivative of the temperature with respect to time. Precipitation of minerals reduces the width of the fissures and thus percolation. Using conventional permeability versus porosity laws, we evaluate the evolution of the permeability field during the hydrothermal circulation. Our computations begin with a uniform permeability and a conductive thermal profile. After imposing a small random perturbation on the initial thermal field, the circulation adopts a finger-like structure, typical of convection in vertical porous slots thermally influenced by surrounding walls. Due to the strong temperature dependence of the fluid viscosity and thermal expansion, the hot rising fingers are strongly buoyant and collide with the top cold stagnant water layer. At the interface of the cold and hot layers, a horizontal boundary layer develops causing massive precipitation. This precipitation front produces a barrier to the hydrothermal flow. Consequently, the flow becomes layered on both sides of the front. The fluid temperature at the top of the layer remains quite low: it never exceeds a temperature of 80°C, well below the exit temperature of hot vent sites observed at black or white 'smokers'. We show that the development of this front is independent of the Rayleigh number of the hydrothermal flow, indicating that the mineral precipitation causes cold, diffusive vents. Finally, we present a model suggesting that the development of smokers is possible when successive tectonic/volcanic events produce a network of new permeable fissures that can overcome the permeability decrease caused by mineral precipitation. Such a model is consistent with recent seismic data showing hydrothermal vents located at seismologically active ridge segments.
Keywords: HYDROTHERMAL VENTS; CONVECTION; POROSITY; DIAGENESIS